Examining the effect of design for additive manufacturing rule presentation on part redesign quality. (1st September 2020) - Fillingim, Kenton Blane; Nwaeri, Richard O.; Paredis, Christiaan J. J.; Rosen, David; Fu, Katherine
Abstract : The main goal of this research is to understand how design for additive manufacturing (DfAM) rule presentation affects a designer's ability to utilise those rules. To that end a pair of studies were carried out. The first study was conducted with industry engineers and designers, while the second study was conducted with students at a university. For both studies, four DfAM design rules for fused deposition modelling (FDM) were chosen, relating to overhangs, planar surfaces, accessible support structures, and part size. Each rule was presented in four different modalities: text only, text with illustration, text with industry example, and text with 3D printed example. Each rule presentation included a justification, and all but the text-only presentation included a 'desirable' and 'undesirable' design example for the rule. Four part redesign problems were given, and the resulting redesigns were then rated on both novelty and quality. Results indicate that although there are no differences in quality and novelty scores between modalities, the text only rules were perceived to be the most difficult to understand. Furthermore, a comparison between the professionals and the students showed that the professionals created higher novelty redesigns. These results have several implications in the field of DfAM education.